Methodical and criminalistics support of court proceedings in criminal cases: current state and perspectives of development - Алєксєйчук, В. І. (Theory and practice of jurisprudence, 2016)
The problems of methodical and criminalistics support of court proceedings in criminal cases nowadays are analyzed taking into consideration new provisions of the current Criminal Procedure Legislation of Ukraine. Need of creation of an independent system of court proceedings methods in criminal cases is proved basing on a comparison with the methodology of crime investigations. Main vectors and perspectives for further scientific researches in this field are defined.